EXPLORING RISK MANAGEMENT IN MALAYSIAN ISLAMIC BANKING – POST FINANCIAL CRISIS LENS - Aman, Nur Amiza (2012)
Risk management of Islamic banks had been a popular subject since the recent global financial crisis as they portrayed stronger resilience against the crisis. Factors such as asset-based financing and low bank's leverage level which is required under Islamic finance framework had itself being the risk mitigation mechanism. Even though IBs on general basis were not significantly affected by recent crisis, there are lessons to be learnt in order to avoid such crisis in the future.